Advances in Cement Analysis and Concrete Petrography - Cong Derek; Broton Don (ASTM International, 2019)
It has been more than 20 years since ASTM International last held a symposium focusing on cement analysis and/or concrete petrography, when ASTM published the Selected Technical Papers (STP) 1215, Petrography of Cementitious Materials. Analytical technology has advanced significantly and many new supplementary cementitious materials have since emerged; as such, it is time to have an overview of the state of the art of development in fields related to cement analysis and concrete petrography.